Tafsir Konten Bahasa Arab: Pandangan Mahasiswa Terhadap Penggunaan Bahasa Arab Di Era Digital - Muhamad Farhan Fauzan; Ihsan Abdul Aziz; Haunan Nisa; Salwa Shofiyyah; Ahmad Fu'adin (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
The purpose of this research is to know and analyze about "Arabic Content Interpretation: Students' Views on the Use of Arabic in the Digital Age". This research aims to examine how students view Arabic content in the digital era. Then what are the challenges faced by students and how are the solutions. This type of research is descriptive qualitative and the data collection technique is through filling out a questionnaire with 42 students as respondents. Data analysis techniques are carried out through several stages, namely: data collection, data processing, descriptive analysis, and data presentation. The results showed that there are several student perspectives related to Arabic content in the digital era. This point of view can be caused by several factors, one of which is the development of information and communication technology such as social media.